2008
DOI: 10.1126/science.1150195
|View full text |Cite
|
Sign up to set email alerts
|

Global Change and the Ecology of Cities

Abstract: Urban areas are hot spots that drive environmental change at multiple scales. Material demands of production and human consumption alter land use and cover, biodiversity, and hydrosystems locally to regionally, and urban waste discharge affects local to global biogeochemical cycles and climate. For urbanites, however, global environmental changes are swamped by dramatic changes in the local environment. Urban ecology integrates natural and social sciences to study these radically altered local environments and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
3,093
2
148

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 5,603 publications
(3,556 citation statements)
references
References 56 publications
26
3,093
2
148
Order By: Relevance
“…Typically, urban green spaces have important ecological effects, contribute to public health, and increase the life quality of urban citizens by offering esthetic enjoyment, recreational opportunities and improvements in physical and psychological well-being (Jo, 2002;Chen and Jim, 2008). Recent reports also found that carbon density in urban areas (23-42 kg C m −2 in sample cities of the United States, Churkina et al, 2010;3.16 kg C m −2 in Leicester, UK, Davies et al, 2011) is comparable to that of some natural forests, and the dynamics of urban vegetation may leave footprints in global biogeochemical cycles (Grimm et al, 2008). The enhancement of green areas has the potential to mitigate the adverse effects of urbanization in a sustainable way (Ridder et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…Typically, urban green spaces have important ecological effects, contribute to public health, and increase the life quality of urban citizens by offering esthetic enjoyment, recreational opportunities and improvements in physical and psychological well-being (Jo, 2002;Chen and Jim, 2008). Recent reports also found that carbon density in urban areas (23-42 kg C m −2 in sample cities of the United States, Churkina et al, 2010;3.16 kg C m −2 in Leicester, UK, Davies et al, 2011) is comparable to that of some natural forests, and the dynamics of urban vegetation may leave footprints in global biogeochemical cycles (Grimm et al, 2008). The enhancement of green areas has the potential to mitigate the adverse effects of urbanization in a sustainable way (Ridder et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…Urban areas are difficult to plan, manage and govern, and have a rapacious appetite for energy and materials, with global environmental impact 7 . Urban challenges ask complex and interrelated questions about equity, justice, resilience, economic opportunity, infrastructure development, ecological restoration and more.…”
Section: Urban Accelerationmentioning
confidence: 99%
“…Numerous similar interactions play out in all corners of the world. The urbanized global society, which accounts for [50% of the world population, depends on the capacity of ecosystems of all kinds worldwide to support urban life with essential ecosystem services (Folke et al 1997;Grimm et al 2008), even though people may not perceive this support or have preferences for it.…”
Section: Introductionmentioning
confidence: 99%